Evaluation of a community-based memory clinic in collaboration with local hospitals to support patients with memory decline - Elbeddini, Ali; Tayefehchamani, Yasamin; Yilmaz, Zekiye; Villegas, Josiah J.; Zhang, Eleen Y. (ELSEVIER, 2022)
Objective: This study evaluates the role of a specialised and multidisciplinary healthcare team, including a phar-macist, in providing medication management for patients with mild cognitive impairment (MCI) and dementia, in a memory clinic. Methods: The study analysed the dataset of 102 patients of a geriatric and memory clinic in a rural area of Ontario, Canada. The case histories of the patients were reviewed a week before the clinic day and a pharmacist performed medication reconciliations. During the clinic day, cognitive tests were conducted and outcomes were discussed with the team, to create a care plan and schedule a follow-up within 3, 6 or 12 months. Results: Most patients had an average of 5 prescriptions and 2 non-prescription medications deprescribed, and 57\% of patients were started on memory-related medi-cations. A total of 712 medications (p-value 0.001) were deprescribed, with 510 prescriptions and 202 non -prescription items. Out of the 712 deprescribed drugs, 374 were discontinued with no therapeutic substitutions, 202 were reduced in dosage and 136 were switched to a safer alternative. A total of 43 patients showed improved Activities of Daily Living (ADL) performance after 3 and 6 months and 68 patients showed improvement after 12 months. Conclusion: This study highlights the importance of a multidisciplinary approach in addressing drug-therapy problems, medication optimisation, and deprescription in patients with dementia. The presence of a pharmacist in the multidisciplinary team enables impactful medication optimisation and leads to improved patient outcomes. This demonstrates the value of specialised expertise in medication management for patients with dementia.
Keywords: Activities of daily living; Dementia; Deprescribing; Memory clinic; Mild cognitive impairment